Sequential MR Imaging of Denervated Muscle: Experimental Study - Bendszus, Martin; Koltzenburg, Martin; Wessig, Carsten; Solymosi, Laszlo (American Journal of Neuroradiology, 2002)
BACKGROUND AND PURPOSE: MR changes in denervated muscles have been reported to occur within days up to several weeks after peripheral nerve damage. The purpose of this experimental study was to investigate the longitudinal changes in denervated muscles by using MR imaging.METHODS: In 12 Lewis rats, the left sciatic nerve was transected at the level of the proximal thigh. MR imaging of both legs was performed before and 1 hour, 24 hours, 48 hours, 7 days, 14 days, 28 days, and 2 months after the procedure. The MR protocol included T1-weighted spin-echo, T2-weighted double turbo spin-echo, and turbo inversion recovery magnitude (TIRM) sequences obtained in the axial plane. Signal intensities (T2-weighted double turbo spin-echo and TIRM sequences) and the T2 TR (T2-weighted double turbo spin-echo sequence) were recorded for the soleus, peroneal, and gracilis muscles of both sides. Moreover, the circumferences of both lower legs were determined on the basis of T1-weighted images.RESULTS: Twenty-four hours after denervation, a signal intensity increase in the denervated peroneal and soleus muscles was present on TIRM images. On T2-weighted images, only the peroneal muscle exhibited slightly increased signal intensities and T2 TR. Forty-eight hours after nerve transection, the denervated soleus and peroneal muscles revealed prolonged T2 TR and marked increased signal intensities on T2-weighted and TIRM images when compared with the contralateral side, which further increased at or less than 2 months after denervation. Muscle atrophy of the denervated muscles was present as early as 7 days after denervation and was also increased at follow-up examinations.CONCLUSION: The TIRM sequence is more sensitive than is T2-weighted imaging in the detection of signal intensity changes in denervated muscle. These changes occur as early as 24 (TIRM sequence) and 48 (T2-weighted sequence) hours, respectively, after complete transection of the sciatic nerve in rats and precede muscle atrophy. The sensitivity to early signal intensity changes in denervated muscles may support the use of MR imaging in the diagnosis of peripheral nerve lesions.